First aid in nursery: integrative literature review (Research, Society and Development, 2022)
The related research deals with an integrative literature review on the importance of first aid in daycare to approach teachers and monitors regarding the knowledge of first aid techniques. Objective: To demonstrate the importance of training teachers and staff in the basics of first aid. Materials and Method: Integrative literature review in the following databases: LILACS, MEDLINE, BIREME and the SCIELO portal. Original articles published in full, in Portuguese, English and Spanish, from 2015 to 2020 were included. Results and discussion: Of the 43 articles found, 15 meet the inclusion criteria. The selected articles were analyzed by author (year), scientific journal, material and methods, relevant public and degree of evidence. Conclusion: From the results found, it can be concluded that teachers and daycare workers are unprepared for urgent and emergency situations, showing fear and insecurity to perform the procedure.